Analisis Hubungan Kadar HbA1c dengan Kadar Glukosa Darah dan Kepatuhan Minum Obat pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Tilamuta, Kabupaten Boalemo, Provinsi Gorontalo - Nurhalmiyanti Nurhalmiyanti; Aloysia Ispriantari (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Type 2 diabetes mellitus is a chronic condition marked by elevated blood glucose levels resulting from insulin resistance and decreased insulin secretion. Effective glycemic control is crucial to prevent complications, and HbA1c is commonly utilized as an indicator of long-term blood glucose levels. This study aimed to examine the relationship between HbA1c levels and blood glucose levels among patients with type 2 diabetes mellitus at Tilamuta Community Health Center, Boalemo Regency, Gorontalo Province. This study employed an analytical cross-sectional design using a total sampling method, involving 557 patients. Data were collected from laboratory records and analyzed through descriptive statistics, the Shapiro-Wilk test for normality, Spearman correlation, and chi-square test. The findings indicated that the average HbA1c level was 7.39%, while the mean blood glucose level was 205.85 mg/dL. A significant and very strong positive correlation was found between HbA1c and blood glucose levels (p=0.000; r=0.862). Furthermore, medication adherence showed a significant association with HbA1c status (p=0.000). These results underscore the role of HbA1c as a dependable marker for assessing glycemic control and highlight the importance of medication adherence in optimizing the management of type 2 diaType 2 diabetes mellitus is a chronic condition marked by elevated blood glucose levels resulting from insulin resistance and decreased insulin secretion. Effective glycemic control is crucial to prevent complications, and HbA1c is commonly utilized as an indicator of long-term blood glucose levels. This study aimed to examine the relationship between HbA1c levels and blood glucose levels among patients with type 2 diabetes mellitus at Tilamuta Community Health Center, Boalemo Regency, Gorontalo Province. This study employed an analytical cross-sectional design using a total sampling method, involving 557 patients. Data were collected from laboratory records and analyzed through descriptive statistics, the Shapiro-Wilk test for normality, Spearman correlation, and chi-square test. The findings indicated that the average HbA1c level was 7.39%, while the mean blood glucose level was 205.85 mg/dL. A significant and very strong positive correlation was found between HbA1c and blood glucose levels (p=0.000; r=0.862). Furthermore, medication adherence showed a significant association with HbA1c status (p=0.000). These results underscore the role of HbA1c as a dependable marker for assessing glycemic control and highlight the importance of medication adherence in optimizing the management of type 2 diabetes mellitus.betes mellitus.